MANUEL CASTELLS: THE IMPACT OF THE NETWORK SOCIETY ON THE NATURE OF SOCIAL COMMUNICATIONS - L. A. Bobova (Vestnik MGIMO-Universiteta)
The article deals with Manuel Castells’ theory of network society, corrected and updated according to the new events happened during the last 10 years. The author of the theory registers the major signals of the changing processes in the modern society, happening due to the expansion of networks in the age of technological innovations. Сhanges affected the global economy, finance, structure of labor, migration, the velocity , role and individual's perception of time. An unprecedented increase of urbanization in the world happened as well. The society became multiethnic. The network structure of the society leads to the uprise of a fundamentally new form of communication called mass selfcommunications. The launched process reduces the elitist role of the official issuer of information i.e. the information flows going vertically, and increases the importance of information published in open spaces on the Internet by individuals i.e. information flows going horizontally from individuals to individuals. New technologies let any individual create its own informational system using the Internet and mobile communication tools. Despite the appearance of mass self-communications in an atmosphere of high social instability, this form of communication turns up to be an effective tool in the matrix of social interaction in the Internet. An accelerated growth in number of mass self-communications’ users is being registered due to the revolutionary changes in the field of communication technologies which made wireless mobile communication devices able to stay connected to the Internet almost continuously. Wireless communication becomes the dominant form of communication in the world, being the fastest-spreading communication technology in history. In this regard the role and form of issue of information in mass-media changes. Synergy between mass-communication and all other forms of communication appeared. The result of this process is the emergence of a radically new culture of communication in modern society.